Mechanisms underpinning remission of albuminuria following bariatric surgery. Issue 5 (October 2016) - Nair, Meera; le Roux, Carel W.; Docherty, Neil G.
Abstract : Purpose of review: Albuminuria is a biomarker of renal injury commonly used to monitor progression of diabetic kidney disease. The appearance of excess albumin in the urine reflects alterations in the structure and permeability of the glomerular filtration barrier. The present article summarizes the clinical evidence base for remission of albuminuria after bariatric surgery. It furthermore focuses on how beneficial impacts on glomerular podocyte structure and function may explain this phenomenon. Recent findings: A coherent clinical evidence base is emerging demonstrating remission of albuminuria following bariatric surgery in patients with obesity and diabetes. The impaired metabolic milieu in diabetic kidney disease drives podocyte dedifferentiation and death through glucotoxic, lipotoxic proinflammatory, and pressure-related stress. Improvements in these parameters after surgery correlate with improvements in albuminuria and preclinical studies provide mechanistic data that support the existence of cause–effect relationship. Summary: The benefits of bariatric surgery extend beyond weight loss in diabetes to encompass beneficial effects on diabetic renal injury. Attenuation of the toxic metabolic milieu that the podocyte is exposed to postbariatric surgery suggests that the restitution of podocyte health is a key cellular event underpinning remission of albuminuria.